Moderne Malerei seit 1945 aus der Sammlung Dotremont. - Kunsthalle Basel; Alvard, Julien; Dotremont, Philippe; Rüdlinger, Arnold (Basel : Kunsthalle Basel, 1961)
Albers, Josef ; Alechinsky, Pierre ; Appel, Karel ; Arp, Hans (Jean) ; Bazaine, Jean ; Benrath, Frédéric ; Bertrand, Gaston ; Brooks, James ; Burri, Alberto ; Capogrossi, Giuseppe ; Crippa, Alberto ; Damian, Horia ; Dubuffet, Jean ; Estève, Maurice ; Fautrier, Jean ; Fontana, Lucio ; Francis, Sam ; Gottlieb, Adolph ; Guiette, René ; Guston, Philip ; Hantaï, Simon ; Hartung, Hans ; Heerbrandt, Henri ; Herbin, Auguste ; Van Hoeydonck, Paul ; Imaï, Toshimitsu ; Jorn, Asger ; Kelly, Ellsworth ; Klein, Yves ; Kline, Franz ; de Kooning, Willem ; Manessier, Alfred ; Mathieu, Georges ; Messagier, Jean ; Miro, Joan ; Mitchell, Joan ; Motherwell, Robert ; Piaubert, Jean ; Poliakoff, Serge ; Pollock, Jackson ; Riopelle, Jean-Paul ; Rothko, Mark ; Sallès, Francis ; Saura, Antonio ; Schneider, Gérard ; Serpan, Jaroslaw ; Smith, Kimber ; Soulages, Pierre ; Tal-Coat, Pierre ; Tàpies, Antoni ; Tobey, Mark ; Ubac, Raoul ; Vasarely, Victor ; van Velde, Bram
biografie
Moderne Malerei : Seit 1945 aus der Sammlung Dotremont, Kunsthalle Basel, 22.4 - 28.5.1961
Duits
Frans
boek